2017
DOI: 10.4081/pb.2016.6402
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming Alleviated Salt Stress Effects on Rice Seedlings by Improving Na+/K+ and Maintaining Membrane Integrity

Abstract: The potential of seed priming by different chemicals on alleviation of growth inhibition of rice (Oryza sativa L.) seedlings under salt stress was investigated. A preliminary experiment using 10 seed-priming chemicals including NaCl, KCl, CaCl 2 , KNO 3 , ascorbic acid (AsA), mannitol, polyethylene glycol (PEG 6000 ), sorbitol, wood vinegar and distilled water revealed that mannitol, KNO 3 and wood vinegar were more effective than the others in alleviating salt-induced growth inhibition of 10-day-old seedlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…This is consistent with the 11%, 28% and 61% increase in chlorophyll content observed in rice (Oryza sativa) plants after 1, 2 and 3 foliar applications of 1:500 wood distillate, respectively [4]. Similarly, chlorophyll increases > 50% compared to controls were observed in 4-week-old rice seedlings after priming seeds with 1:100, 1:300 and 1:1000 wood distillate [5]. In addition, mustard (Sinapis arvensis) plants grown in soils added biweekly with 1:500 wood distillate showed increases in chlorophyll content of ca.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with the 11%, 28% and 61% increase in chlorophyll content observed in rice (Oryza sativa) plants after 1, 2 and 3 foliar applications of 1:500 wood distillate, respectively [4]. Similarly, chlorophyll increases > 50% compared to controls were observed in 4-week-old rice seedlings after priming seeds with 1:100, 1:300 and 1:1000 wood distillate [5]. In addition, mustard (Sinapis arvensis) plants grown in soils added biweekly with 1:500 wood distillate showed increases in chlorophyll content of ca.…”
Section: Discussionsupporting
confidence: 86%
“…Wood distillate, also known as pyroligneous acid or wood vinegar, is one of these bio-based products which is empirically known for providing several benefits to agricultural plants, e.g., limiting the action of pathogens and increasing their productivity [3]. Among the most investigated effects related to the application of wood distillate to plants is the increase in biomass [4,5] and in the number of fruits along with their size [6,7]. In addition, also positive effects on the chlorophyll content and the photosynthetic rate are reported [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Treat-ing seeds with wood vinegar also has the effect of improving crop resistance. Seed soaking in a wood vinegar solution can significantly increase the content of abscisic acid and the activity of antioxidant enzymes in the roots of wheat under drought conditions by reducing the content of malondialdehyde, and thus improve the drought resistance of wheat [26] and reduce the damage of salt stress to rice seedlings [48]. These studies have confirmed that wood vinegar can increase the antioxidant capacity by enhancing the activity of antioxidant enzymes such as superoxide dismutase and regulate the content of osmotic substances such as proline and soluble protein to reduce the osmotic potential of cells and reduce cold stress.…”
Section: Wood Vinegar Can Improve the Abiotic Stress Resistance Of Ramentioning
confidence: 99%
“…Ten primed seeds were transferred to sterile filter paper in Petri dishes (90-mm diameter) containing 5 ml of sterilized deionized water (control) or 150 mM NaCl (salt treatment). The concentration of NaCl used in this study followed that by Theerakulpisut et al (2016). Seeds were incubated in darkness at 25 °C.…”
Section: Seed Primingmentioning
confidence: 99%